2003
DOI: 10.1128/mcb.23.8.2821-2833.2003
|View full text |Cite
|
Sign up to set email alerts
|

NPAT Expression Is Regulated by E2F and Is Essential for Cell Cycle Progression

Abstract: NPAT is an in vivo substrate of cyclin E-Cdk2 kinase and is thought to play a critical role in coordinated transcriptional activation of histone genes during the G 1 /S-phase transition and in S-phase entry in mammalian cells. Here we show that NPAT transcription is up-regulated at the G 1 /S-phase boundary in growthstimulated cells and that the NPAT promoter responds to activation by E2F proteins. We demonstrate that endogenous E2F proteins interact with the promoter of the NPAT gene in vivo and that induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 55 publications
2
71
0
Order By: Relevance
“…Additionally, there was no apparent homogeneity of function among these factors, except that most fitted into the categories related to cell cycle regulation and DNA recombination and repair. Of the five proteins affected by the most effective siRNAs, SETD8 is a SET domain containing lysine methyltransferase (37), CASP8AP2 is a component of the apoptotic machinery (38), SOX15 is a developmental transcription factor (39), TROAP is a cell adhesion molecule reported to mediate blastocyst implantation (40), and NPAT is a cell cycle progression regulator encoded within the ATM gene (41). This heterogeneity of function might indicate that AAV transduction is regulated at multiple levels or that, more likely, the knockdown of these factors converge into common intracellular signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there was no apparent homogeneity of function among these factors, except that most fitted into the categories related to cell cycle regulation and DNA recombination and repair. Of the five proteins affected by the most effective siRNAs, SETD8 is a SET domain containing lysine methyltransferase (37), CASP8AP2 is a component of the apoptotic machinery (38), SOX15 is a developmental transcription factor (39), TROAP is a cell adhesion molecule reported to mediate blastocyst implantation (40), and NPAT is a cell cycle progression regulator encoded within the ATM gene (41). This heterogeneity of function might indicate that AAV transduction is regulated at multiple levels or that, more likely, the knockdown of these factors converge into common intracellular signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear Protein, Ataxia-Telangiectasia Locus (NPAT/ p220) stimulates the transcription of all replicationdependent histone genes during S phase (Gao et al, 2003;Ye et al, 2003) in a phosphorylation-dependent manner (Zhao et al, 1998(Zhao et al, , 2000Ma et al, 2000). NPAT functions, in part, by recruiting coactivator proteins including histone-modifying enzymes (DeRan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…NPAT functions, in part, by recruiting coactivator proteins including histone-modifying enzymes (DeRan et al, 2008). Moreover, NPAT transcription is regulated in a cell cycle-dependent manner by the E2F family of transcription factors (Gao et al, 2003). However, no role for NPAT in histone mRNA 3 0 end processing has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…NPAT is a newly discovered target gene of E2F-1 (Gao et al, 2003) and we wanted to know if NPAT is also repressed by induced HES-1 expression in T47D cells. By using the T47D dnHES-1 cell line, we found that treatment with atRA prevented E 2 induction of NPAT mRNA, while expression of dnHES-1 reversed the effects of atRA (Figure 4b).…”
Section: Hes-1 Expression Arrests T47d Cells In the G 1 Phase Of The mentioning
confidence: 99%